2022
DOI: 10.3389/fimmu.2021.815840
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated TP53 Among PTSD Patients Leads to Downregulation of miRNA let-7a and Promotes an Inflammatory Th17 Phenotype

Abstract: Post-traumatic stress disorder (PTSD) is a psychiatric disorder and patients diagnosed with PTSD often express other comorbid health issues, particularly autoimmune and inflammatory disorders. Our previous reports investigating peripheral blood mononuclear cells (PBMCs) from PTSD patients showed that these patients exhibit an increased inflammatory T helper (Th) cell phenotype and widespread downregulation of microRNAs (miRNAs), key molecules involved in post-transcriptional gene regulation. A combination of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…The pharmacological study suggested that G. baccata extract can upregulate AKT1 gene expressions to protect the cells against oxidative damage and inflammation ( Martínez et al, 2021 ). Moreover, the studies also suggested that TP53, PIK3R1, and PIK3CA were vital for inflammation ( Eyileten et al, 2018 ; Busbee et al, 2021 ; Reske et al, 2021 ). Accordingly, the results indicate that emodin, aloe-emodin, rhein, luteolin, and quercetin may play an important role in inhibiting anti-inflammatory and anti-oxidative damage.…”
Section: Resultsmentioning
confidence: 98%
“…The pharmacological study suggested that G. baccata extract can upregulate AKT1 gene expressions to protect the cells against oxidative damage and inflammation ( Martínez et al, 2021 ). Moreover, the studies also suggested that TP53, PIK3R1, and PIK3CA were vital for inflammation ( Eyileten et al, 2018 ; Busbee et al, 2021 ; Reske et al, 2021 ). Accordingly, the results indicate that emodin, aloe-emodin, rhein, luteolin, and quercetin may play an important role in inhibiting anti-inflammatory and anti-oxidative damage.…”
Section: Resultsmentioning
confidence: 98%
“…Busbee et al [ 52 ] reported miR-let-7a as the most significantly downregulated tumor protein (TP53) associated miRNA in PTSD PBMCs compared to controls and was shown to regulate CD4 + T helper-17 (Th17) cells negatively. The downregulation of TP53 and miR-let-7a could lead to abnormal inflammatory TH17 responses in PTSD.…”
Section: Dysregulated Mirnas In Ptsdmentioning
confidence: 99%
“…PTSD patients exhibited widespread downregulation of miRNAs in peripheral blood mononuclear cells and were linked to tumor protein 53 (TP53; Busbee et al, 2022 ). The level of the TP53-associated miRNA Let-7a was significantly downregulated in PTSD patients, influencing inflammatory T helper (Th) cells by altering the production of interleukins (IL-6 and IL-17).…”
Section: Molecular Mechanisms Affecting the Fear Circuitry In Ptsdmentioning
confidence: 99%
“…Traumatic stress significantly downregulated the expression of miRNA-598-3p in the BLA, increasing the susceptibility of males to fear conditions (Jones et al, 2019). PTSD patients exhibited widespread downregulation of miRNAs in peripheral blood mononuclear cells and were linked to tumor protein 53 (TP53; Busbee et al, 2022). The level of the TP53-associated miRNA Let-7a was significantly downregulated in PTSD patients, influencing inflammatory T helper (Th) cells by altering the production of interleukins .…”
Section: Genetic and Epigenetic Regulationmentioning
confidence: 99%